Effect of a Cardiopulmonary Resuscitation Coach on Workload During Pediatric Cardiopulmonary Arrest: A Multicenter, Simulation-Based Study. Issue 5 (May 2020) - Tofil, Nancy M.; Cheng, Adam; Lin, Yiqun; Davidson, Jennifer; Hunt, Elizabeth A.; Chatfield, Jenny; MacKinnon, Laura; Kessler, David
Abstract : Objectives: Optimal cardiopulmonary resuscitation can improve pediatric outcomes but rarely is cardiopulmonary resuscitation performed perfectly despite numerous iterations of Basic and Pediatric Advanced Life Support. Cardiac arrests resuscitation events are complex, often chaotic environments with significant mental and physical workload for team members, especially team leaders. Our primary objective was to determine the impact of a cardiopulmonary resuscitation coach on cardiopulmonary resuscitation provider workload during simulated pediatric cardiac arrest. Design: Multicenter observational study. Setting: Four pediatric simulation centers. Subjects: Team leaders, cardiopulmonary resuscitation coach, and team members during an 18-minute pediatric resuscitation scenario. Interventions: National Aeronautics and Space Administration-Task Load Index. Measurements and Main Results: Forty-one teams (205 participants) were recruited with one team (five participants) excluded from analysis due to protocol violation. Demographic data revealed no significant differences between the groups in regard to age, experience, distribution of training (nurse, physician, and respiratory therapist). For most workload subscales, there were no significant differences between groups. However, cardiopulmonary resuscitation providers had a higher physical workload (89.3 vs 77.9; mean difference, –11.4; 95% CI, –17.6 to –5.1; p = 0.001) and a lower mental demand (40.6 vs 55.0; mean difference, 14.5; 95% CI, 4.0–24.9; p = 0.007) with a coach (intervention) than without (control). Both the team leader and coach had similarly high mental demand in the intervention group (75.0 vs 73.9; mean difference, 0.10; 95% CI, –0.88 to 1.09; p = 0.827). When comparing the cardiopulmonary resuscitation quality of providers with high workload (average score > 60) and low to medium workload (average score < 60), we found no significant difference between the two groups in percentage of guideline compliant cardiopulmonary resuscitation (42.5% vs 52.7%; mean difference, –10.2; 95% CI, –23.1 to 2.7; p = 0.118). Conclusions: The addition of a cardiopulmonary resuscitation coach increases physical workload and decreases mental workload of cardiopulmonary resuscitation providers. There was no change in team leader workload.